(untitled) (Research, Society and Development, 2022)
Eating patterns and habits have been changing in recent years due to several factors, especially the numerous attributions that the globalized world requires. Experts have pointed out that food advertising has negatively influenced children´s eating habits and health. This article is an integrative review and was structured through bibliographic research carried out on scientific articles, dissertations and theses located in electronic publications, on Google Scholar, Scielo (Scientific Eletronic Library Online) and PubMed platforms. To search for bibliographic materials, the following keywords were used: child food consumption, childhood obesity, social media, digital communication, digital generations. This study aimed to identify the influence of social media and digital communication, digital generations. This study aimed to identify the influence of social media and digital technologies on the formation of eating behavior and children´s health. Studies indicate that advertisements for extremely high-calorie and low-nutrition foods are increasing since early childhood, a stage of greater vulnerability and formation of eating habits, generating a considerable increase in NCDs. The results showed that children are attracted to the artifices that the media use, as well as the way they are applied in everyday life, often hiding their consequences throughout life.